Biochar Improves Plant Growth and Reduces Nutrient Leaching in Red Clay Loam and Sandy Loam (Hydro Nepal: Journal of Water, Energy and Environment, 2012)
A factorial pot experiment was conducted using two types of soils (sandy loam and red clay loam) that are commonly used for commercial vegetable production in Bundaberg, region of Central Queensl and Australia. The soils were amended with 0, 25, 50 and 75 t/ha of green waste biochar and minimum doses of N, P and K (30 kg/ha, 30 kg/ha and 40 kg/ha respectively). After two weeks of plant establishment, the pots were leached with 1.5 litres of deionised water at week intervals, and cation concentrations of the leachate were determined. In 25 t/ha biochar treatment, there was a significant (P